Sistem Penggajian Karyawan pada Sekar Anugrah Penglipuran Nursery Kabupaten Bangli Provinsi Bali - PUSPAYANTI, NI PUTU DEVI; DARMAWAN, DWI PUTRA; DEWI, IDA AYU LISTIA (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.13, No.2, Desember 2024, 2024)
Employee Payroll System at Sekar Anugrah Penglipuran Nursery, Bangli Regency, Bali Province.  Sekar Anugrah Penglipuran Nursery is an ornamental plant production company established in 2017. Sekar Anugrah Penglipuran Nursery, in an application, follows a system that provides district/city minimum wages. Where every activity carried out by employees, if they reach the target in product sales, will receive incentives or bonuses according to the agreement at the beginning, which distribute every three months. The type of data used in this research is quantitative and qualitative data related to the problem under study, including an overview of the research location, the characteristics of the respondents, the factors that determine the payroll system, and the purpose of the payroll system at Sekar Anugrah Penglipuran Nursery. Surveys and interviews using questionnaires. The results showed that each indicator on each variable in Sekar Anugrah Penglipuran Nursery had an MSA value of > 0.50. That means that the correlation between indicators is vital so that the four variables significantly used influence the payroll system of Sekar Anugrah Payroll Nursery. Namely payroll techniques, payroll procedures, payroll structure, mix payroll, government support, payroll policies, and payroll systems. Each variable has one component greater than one, namely components with variance values for each variable of 69.212%, 69.498%, 77.206%, 76.308%, 69.212%, and 63.867%. That shows that it is true that the number of factors formed in six factors. Then the suggestion for Anugrah Penglipuran Nursery Bangli Regency Bali Province, the employee payroll system provided must be improved and improved to help achieve employee satisfaction so that it will increase employee performance and loyalty.